Increasing flower longevity in Alstroemeria - Chanasut U. (2014)
The vase-life of Alstroemeria (cv. Rebecca) flowers is terminated when the tepals abscise. Abscission was accelerated by both chloroethylphosphonic acid (CEPA) and 1-aminocyclopropane-1-carboxylic acid (ACC). Petals abscised 24 h earlier compared with controls, when isolated cymes were placed in 340 nM CEPA, and earlier still when higher concentrations were used. This suggests that flowers of this Alstroemeria cultivar are very ethylene sensitive. Treatment with silver thiosulphate (STS) overcame the effects of exposure to CEPA and delayed perianth abscission of untreated isolated flowers by 3-4 days. The inclusion of 1% sucrose in the vase solution also extended longevity but not by as much as STS treatment; combined STS and sucrose treatments did not increase longevity beyond that of either treatment alone. However, removal of the young buds from the axil of the first flower was the most effective treatment to extend vase-life and encouraged the growth and development of the remaining flower. Flowers on cut inflorescences from which young axillary buds were trimmed more than doubled in fresh weight 6 days after flower opening compared with an increase of only 70-80% in those untreated or treated with STS and/or sucrose. Growth was less in isolated cymes but followed a similar pattern. The effect of STS and/or sucrose treatment was synergistic with the trimming treatment and thus the vase-life of trimmed, STS and sucrose-treated flowers was over 7 days longer than that for untreated controls. © 2003 Elsevier B.V. All rights reserved.